Gestión administrativa – financiera – contable y su incidencia en la rentabilidad de la distribuidora Quevedo S.A (Diquesa) en el periodo 2012 – 2013, Manual de control - Tubay Segovia, Diana Mariela (2015)
Business enterprises in the competitive field of market commercial and social objectives to be met by the mission raised; one of the functions of the organizations is to systematize the business planning with the internal control system that is necessary to design and establish areas of operations and institutional policies for actions carried out and facilitate compliance with established plans and programs, channeling good use of its resources to ensure the profitability of the company. The feasibility of the results of this research, it was possible to get them through the design and implementation of techniques and instruments, such as interviews, surveys, observations were applied to the sample of the investigation including owners, staff distribution, taking to guide the functional organic system of the institution of the company having examined the investigations carried out allowed me to test hypotheses conclusions inherent in the research and recommendations to overcome the problem of investigation by the proposal made in the document. The general hypothesis Manuel Designing an Administrative Internal Control – Finance for Quevedo Distribuidora S.A “DIQUESA“ that allow you to improve your performance and compete in the market by consumers.